2019
DOI: 10.3390/computers8030069
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Framework for Assessing IT Strategy Execution

Abstract: In this paper, we explore a framework for assessing the implementation of IT Strategic planning, grounded in the combination and iteration of different methods. It is a part of an Action Design Research exercise being made up at a leading online European university. The assessment mixes three main dimensions (strategy, performance and governance), extracted from the professional and academic research. Its application to this context through a varied scaffolding of methods, tools and techniques seems robust and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…(2020) emphasized the critical need of the organizational role of human resources and their contribution to effective strategic alignment. Rodríguez et al. (2019) explored a framework for assessing the implementation of IT strategic planning and found that IT strategy execution and project portfolio management are important factors for IS success.…”
Section: Related Workmentioning
confidence: 99%
“…(2020) emphasized the critical need of the organizational role of human resources and their contribution to effective strategic alignment. Rodríguez et al. (2019) explored a framework for assessing the implementation of IT strategic planning and found that IT strategy execution and project portfolio management are important factors for IS success.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of the UOC -a fully online university with 75.000 students based in Barcelona (Spain) -corporate governance has been implemented over the last years on a continuous basis. We can highlight the following milestones: An account of the UOC IT strategic management approach has been provided by Rodríguez et al (2019).…”
Section: Strategic Ict Governance and Investment Decisionsmentioning
confidence: 99%